Study of Biochemical Markers Related to Urinary Tract Infection UTI - Khadhim, Huda Hamza; Wthej, Manar Faris Malik; Kazim, Ronaq Radhi Hassoun; Abis, Fatima Abdul Kazim Khadir (American Journal of Biomedicine and Pharmacy, 2025)
Urinary tract infection is an infection that begins with the urinary system. The UTI is one of the common diseases, as it increases in females. More than males, at a rate of 56% in females and 44% in males, due to the shorter urethra in females than in males. This study was designed to investigate some biochemical parameters related to UTI, where this disease is one of the most serious health problems that face large numbers of people annually. The research was included the collecting results of the following tests (calcium oxalate, uric acid, urea, creatinine, and C-reactive protein). In addition, the data for 100 participants, who were included 51 women (28 patients and 23 healthy control) and 49 men (29 patients and 20 healthy control), were collected from the Hospital of Imam Hassan (AS) at the holly city of Karbala during the period from November 14, 2021, to January 13, 2022 (three months), of both sexes and in different age groups. The results were also statistically analyzed using Chi-square, T test and Man-Whitney tests. The results showed the following:Females are more susceptible to infection compared to males. In the uric acid test, no change was observed in the results, whether for patients or normal persons. In the test of urea and creatinine, an increase in their concentrations was observed by a relatively large percentage for patients.In the calcium oxalate test, the statistical analysis of the data shows that there is a significant difference between healthy and sick patients. In the CRP test, an increase in its concentration in patients.Consequently, it can be concluded that the chances of women getting a urinary tract infection are more than men, because the nature of the urinary system of women is different from that of men.